A concepção dialética do estado e o primado republicano - Gustavo Felipe Melo da Silva (2017)
To understand the Concept of State, we must manage its elements such as people, territory and Government structured over the law, all within the historic dynamics of the time. The State is the product of the dialectical developmental process of the interaction of those elements, simultaneously. The State must be seen as a whole. This implies that only if we conceive that individual, society and State are the same thing, because they consist total unit, is possible to understand the State, and therefore, their structural legal principles. In this way the intention is to use, practically, the logic and dialectical thinking to effectively achieve the comprehension of the State. It is to understand the State as a Concept. We have in mind the premise that the State must be guided by preservation and completion of the common good, and that the notion of common good, general welfare finds its correlate in the legal terminology as the public interest. Hence, we want to demonstrate that the public interest is the interest of the State, in its design State as a Concept, within the The Dialetic Conception of the State. The interpretative key governing Republican's postulate is the public interest, which brings both the moment of Political Power and Civil Society within itself, dialectically structured. Indeed, for the possibility of the concrete realization of what is being proposed, under the jus-political-philosophical perspective, we will seek to elucidate the content of Democratic-Republican Principle. It is, therefore, of the port that enables, at least initially, the concrete realization of the conception of the State as a Concept.